Pengetahuan dan Sikap dengan Kecemasan pada Wanita Menopause - Asikin, badria; Lestari, Ima Mustika Tri; Bahrum, Sri Wahyuni (Sarana Ilmu Indonesia (salnesia), 2024)
Knowledge has an important role in determining a person's level of anxiety. Knowledge and experience possessed by a person can also determine the person's attitude in life. The purpose of this study was to determine the relationship between knowledge and attitudes towards anxiety in menopausal women in the Maricaya sub-district. The research sample was 40 people. The research instrument was an observation sheet of questions about the knowledge of menopausal mothers and an observation sheet of questions about the attitude of menopausal women about changes during menopause. Statistical test results using the chi-square test obtained a value of p = 0,008, which means it is smaller than α (0,05). Thus, the research hypothesis was declared accepted, meaning that there was a relationship between knowledge and the anxiety level of menopausal women. Statistical testing using the chi-square test obtained a value of p = 0,011, which means it is smaller than α (0,05). Thus, the research hypothesis is declared accepted, meaning that there is a relationship between attitude towards the anxiety level of menopausal women. The conclusion of this research is that all knowledge and attitudes have a relationship with the level of anxiety in postmenopausal women in the Maricaya sub-district